Spatial patterns and predictors of antenatal care interruption in war-torn Tigray, northern Ethiopia: Spatial modelling approach - Assefa Ayalew Gebrselassie; Mussie Alemayehu; Haftu Gebrehiwot; Brhane Ayele; Hailay Gebretnsae; Ferehiwot Hailemariam; Tsegay Wellay; Adhena Ayalew; Araya Abrha Medhanyie; Znabu Hadush Kahsay; Liya Mamo; Mebrahtu Kalayu Chekole; et al. (PLoS ONE, 2025)
Introduction Antenatal care (ANC) is vital for maternal health, yet its provision has been severely disrupted in conflict-affected Tigray, Ethiopia. This study employs a community-based approach to analyze the spatial patterns and predictors of ANC interruption in conflict-affected, Tigray region, northern Ethiopia. Methods and materials A cross-sectional design was used, to select 2,444 eligible women from 13,915 women of reproductive age across from six zones and 57 clusters. Multistage cluster sampling was employed to approach the study participants. Data were collected using structured questionnaires, and geographic coordinates were obtained for spatial geo-points. A spatial logistic regression model was used to assess the effects of geographic and socio-demographic factors on ANC interruptions, accounting for spatial dependencies. Results The prevalence of ANC interruption was24.8% (n = 605, 95% CI: 23.1%, 26.5%). Each additional minute of travel increased the log-odds of interruption by 0.000353 (SE = 0.0001, p < 0.001. Geographic zone significantly influenced ANC interruptions, with women in the southeast and eastern zones experiencing lower log-odds compared to the northwest zone. Moreover, having more under- five children raised the log-odds of ANC interruption by 0.083 (SE = 0.01, p < 0.001). Households without a radio had a 0.089 lower log-odds of ANC interruption (SE = 0.033425, p = 0.007), highlighting the importance of access to information. The war’s impact was significant, with 96.5% (2,358, 95% CI: [95.4%, 97.6%]) reporting a family member was disabled; of these, 72.7% (1,778, 95% CI: [71.0%, 74.4%]) did not postpone their ANC visit, while 23.7% (580, 95% CI: [22.2%, 25.2%]) did. Conclusions The findings revealed a significant ANC interruption in Tigray, influenced by geographic disparities, household dynamics, and information access. Improving infrastructure and security, implementing targeted interventions, enhancing mass media health information dissemination, and further research on geographic disparities are essential.